Exploring Love Brands Among Young Czechs - Ďurka, Sebastian; Karlíček, Miroslav, 1979-; Hrivnák, Tomáš; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This Master's thesis explores the conceptualisation, antecedents, and outcomes of brand love among young Czechs aged 18 to 25. Despite the widespread use among marketers, a clear theoretical consensus remains unestablished. At the same time, brand love has become a subject of diverse academic views and criticism from scholars and marketing professionals. This qualitative research explores the conceptualisation, antecedents, and outcomes of brand love within this demographic by analysing eleven semi-structured interviews with Czech university students. The research findings validate the applicability of the famous brand love model and suggest adaptations related to the prevalence of habitual behaviours and the dimension of functional separation distress. Brand love emerges from key antecedents such as perceived quality, visual appeal, early emotional connections, nostalgia, continuous positive experiences, social influences, and self-expression with an alignment of personal values. The outcomes of brand love are linked to increased brand advocacy and a willingness to pay premiums. Yet, brand loyalty, influenced by emotional attachments and habitual consumer behaviours, varies across product categories, especially as rational considerations emerge. Emotional connections were perceived as strongest in aspirational brands and high-involvement categories like electronics, while practical considerations prevailed in the food and beverages product category. Importantly, this study reveals that brand love extends beyond satisfaction with brands that are owned while being even more common towards brands one aspires to own in the future, fundamentally resetting the prior academic views and definitions that linked brand love solely to a satisfied consumer.
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses